2008
DOI: 10.1002/uog.6141
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal prediction of neonatal morbidity in survivors with congenital diaphragmatic hernia: a multicenter study

Abstract: K E Y W O R D S:congenital diaphragmatic hernia; lung area; lung to head ratio; postnatal morbidity; prenatal diagnosis ABSTRACT Objectives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
155
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(162 citation statements)
references
References 23 publications
4
155
0
3
Order By: Relevance
“…Three dimensional estimation of the fetal lung volume, calculation of the right lung area to thoracic area ratio, and calculation of the lung to thoracic circumference ratio are three different measurements that may correlate with neonatal outcome, but the lung-to-head ratio has been the most widely used prognostic indicator. [4,5] The most severely affected infants develop respiratory distress at birth, whereas a majority demonstrates respiratory symptoms within the first 24 hours of life. Most CDH's present in the first 24 hours of life, 10% to 20% of the infants with this defect present later.…”
Section: Discussionmentioning
confidence: 99%
“…Three dimensional estimation of the fetal lung volume, calculation of the right lung area to thoracic area ratio, and calculation of the lung to thoracic circumference ratio are three different measurements that may correlate with neonatal outcome, but the lung-to-head ratio has been the most widely used prognostic indicator. [4,5] The most severely affected infants develop respiratory distress at birth, whereas a majority demonstrates respiratory symptoms within the first 24 hours of life. Most CDH's present in the first 24 hours of life, 10% to 20% of the infants with this defect present later.…”
Section: Discussionmentioning
confidence: 99%
“…The same prenatal features also predict early neonatal morbidity, such as the need for prosthetic patch repair, duration of assisted ventilation and incidence of feeding problems 21 .…”
Section: Introductionmentioning
confidence: 99%
“…There were however a few exceptions such as days in the NICU and the occurrence of PHT that did not respond to iNO, which apparently are very much influenced by prenatal severity indicators. Though only partial, also the earlier-described relationship between the O/E LHR and selected neonatal morbidity parameters was confirmed [20,52]. Why this was not so for all parameters may be due to the case mix in this cohort, which is very different from the more representative population in the antenatal CDH registry [20].…”
Section: Discussionmentioning
confidence: 58%
“…Several studies have demonstrated its predictive value, including a meta-analysis [16,17,18,19]. The O/E LHR has also been shown to predict early neonatal morbidity [20]. Measurement of the bilateral lung volume can be done either by three-dimensional ultrasound or fetal MRI.…”
Section: Introductionmentioning
confidence: 99%